Tailoring treatment of haemophilia B: accounting for the distribution and clearance of standard and extended half-life FIX concentrates - Iorio, Alfonso; Fischer, Kathelijn; Blanchette, Victor; Rangarajan, Savita; Young, Guy; Morfini, Massimo; for the Pharmacokinetic (PK) Expert Working Group of the International Prophylaxis Study Group (the IPSG) (Thrombosis and Haemostasis, 2017)
The prophylactic administration of factor IX (FIX) is considered the most effective treatment for haemophilia B. The inter-individual variability and complexity of the pharmacokinetics (PK) of FIX, and the rarity of the disease have hampered identification of an optimal treatment regimens. The recent introduction of extended half-life recombinant FIX molecules (EHL-rFIX), has prompted a thorough reassessment of the clinical efficacy, PK and pharmacodynamics of plasma-derived and recombinant FIX. First, using longer sampling times and multi-compartmental PK models has led to more precise (and favourable) PK for FIX than was appreciated in the past. Second, investigating the distribution of FIX in the body beyond the vascular space (which is implied by its complex kinetics) has opened a new research field on the role for extravascular FIX. Third, measuring plasma levels of EHL-rFIX has shown that different aPTT reagents have different accuracy in measuring different FIX molecules. How will this new knowledge reflect on clinical practice? Clinical decision making in haemophilia B requires some caution and expertise. First, comparisons between different FIX molecules must be assessed taking into consideration the comparability of the populations studied and the PK models used. Second, individual PK estimates must rely on multi-compartmental models, and would benefit from adopting a population PK approach. Optimal sampling times need to be adapted to the prolonged half-life of the new EHL FIX products. Finally, costs considerations may apply, which is beyond the scope of this manuscript but might be deeply connected with the PK considerations discussed in this communication.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Haemophilia B; factor IX; pharmacokinetics; extended half-life; tailored; personalised